Un catalogo per la collezione di Francesco Molinari (ACME, 2023)
After having disclosed a part of the life and commercial activity of Giulio Sambon (1837-1921) and his «Impresa di Vendite in Italia» in Milan, Florence, Rome and Naples, this paper proposes to deep his encounter with another art dealer: Francesco Molinari (1813-1866). He lived in Milan in the second half of the 19th century and could have probably been a meeting point for collectors and connaisseurs of that time. Thanks to the sale he asked Sambon to organize to close his shop in Milan, it is possible to recognize his predilection for artworks of Renaissance time coming from Lombardy, responding to the current taste spread in the city and the new studies of critics. This event and the related documentation here presented – art catalogues and certificates for the exportation, that mix information about art-history and taste too – show the path of this collection, which counted more than 350 artworks and got to dissolution.